Integrated traditional Chinese and western medicine nursing of a patient with vestibular neuritis accompanied by medullary infarction (1例前庭神经炎伴延髓梗死患者的中西医结合护理体会) - BAI Li (白丽) (Association of Integrative Nursing, 2024)
This article summarized the integrated traditional Chinese and western medicine nursing of a patient with vestibular neuritis accompanied by medullary infarction. Comprehensive nursing interventions such as lifestyle support, dietary guidance, vestibular function rehabilitation exercise and psychological care were carried out. According to the clinical symptoms analysis and syndrome differentiation, Traditional Chinese Medicine nursing techniques including auricular acupoint pressing, moxibustion, Chinese herb medicine foot bath, Chinese herb medicine collapse and acupuncture were conducted to relieve the dizziness symptoms and improve the body constitution and health of the patient. (本文总结1例前庭神经炎伴延髓梗死患者的中西医结合护理经验。根据疾病证型, 在生活护理、饮食护理、前庭康复训练、心理护理等常规护理措施的基础上, 结合中医辨证施护, 采取耳穴压丸、艾灸、中药泡足、中药塌渍、针灸等中医特色护理技术, 有效缓解患者的头晕症状, 改善患者体质, 对促进患者健康起到积极作用。)